ANALYSIS OF PROVIDING REPRODUCTIVE HEALTH EDUCATION FOR ADOLESCENTS BEFORE MENARCHE IN SUPPORT GROUPS IN MOJOKERTO CITY PRIMARY SCHOOLS - Dewi, Catur Prasastia lukita (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Adolescence is a very important period in human life, because it is a transition from childhood to adulthood. Many teenagers experience difficulties in dealing with their first menstruation (menarche) if they have not received the right information from their surrounding support groups, including parents, family members, teachers or their immediate environment. This research aims to analyze the provision of reproductive health education for adolescents approaching menarche in support groups at SDN Mojokerto City. The research method used was pre-experimental. The instrument is a questionnaire to assess knowledge. The sample in this study consisted of 56 parents, 56 students and 28 teachers. The results of this research showed that there was a significant influence on the treatment given to each sample, indicated by a significance value of 0.000 < 0.005 in the peer support group, and a significance value of 0.000 < 0.005 in the parent support group, while in the teacher support group significant results show 0.001 < 0.005. Based on the results, it can be concluded that reproductive health education which is carried out effectively has an impact on increasing knowledge of reproductive health in the three support groups, including peers, parents and teachers.